IMPLEMENTASI PENERAPAN APLIKASI MOBILE BANKING BTN DALAM MENDUKUNG TRANSAKSI NON-TUNAI NASABAH DI BANK TABUNGAN NEGARA (PERSERO) Tbk CABANG MEDAN - Zega, Historisman; Karo, Jani Putri Nasrani Br; Purba, Putri Damai Yanti; Rajaguguk, Particia Herpayanti; Siagian, Nalom (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
During the internship at PT. Bank Tabungan Negara (Persero) Tbk, the author gained experience in understanding the working world, especially in the field of business administration. During the internship, the author carried out various activities such as entering customer data, ensuring the completeness of archive documents, writing credit agreement numbers (PK), deeds of sale and purchase (AJB), certificates, building permits (IMB), power of attorney for encumbrance rights (SKMHT), deeds of encumbrance rights (APHT), and certificates of encumbrance rights (SHT), fire insurance policies, and notary names on document envelopes, compiling and storing Customer Information Files (CIF), Recap daily m-banking data, check the completeness of the People's Business Credit (KUR) application documents of customers, participate in field surveys of the business locations of prospective People's Business Credit (KUR) customers, assist in filling out the OTS form or the results of interviews with prospective People's Business Credit (KUR) customers. The author is familiar with the procedures for customer data entry, customer account opening, and the application and granting of People's Business Credit (KUR). This experience has helped improve the author's skills, particularly in the fields of business administration, responsibility, and adaptability in a professional environment. From the author's observations, the implementation of mobile banking at PT. Bank Tabungan Negara (Persero) Tbk has been running well, although there are still many obstacles in using the BTN Mobile application, including limited digital literacy among certain groups and technical obstacles such as internet network disruptions or system errors in the application.